2022
DOI: 10.3390/agronomy12051100
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Economic Efficiency of Water Use through a Household Farmer Survey in North China

Abstract: Water use efficiency (WUE) is one of the most widely used indicators in agricultural water management. Although this indicator has obvious advantages, it is limited to measuring the relationship between crop yield and corresponding water use. In recent years, many researchers have noted that understanding the economic efficiency of water use (EEWU) could have great water-saving potential, while it has been poorly investigated with respect to China’s agricultural water management. This paper assesses EEWU throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Some empirical studies concluded that the key to saving agricultural water is to compress the irrigation quota of water-intensive crops, such as reducing the planting area of winter wheat in China [9][10][11][12][13][14]. In addition, making full use of natural precipitation and improving the water use efficiency of crops are also critical to alleviate water scarcity [15,16]. Studying the irrigation water demand and water deficit of different crops is vital for determining reasonable irrigation water quota [17].…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical studies concluded that the key to saving agricultural water is to compress the irrigation quota of water-intensive crops, such as reducing the planting area of winter wheat in China [9][10][11][12][13][14]. In addition, making full use of natural precipitation and improving the water use efficiency of crops are also critical to alleviate water scarcity [15,16]. Studying the irrigation water demand and water deficit of different crops is vital for determining reasonable irrigation water quota [17].…”
Section: Introductionmentioning
confidence: 99%